2021
DOI: 10.7717/peerj.10661
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards stem cells and the significance of their medical application among healthcare sciences students of Jouf University

Abstract: Background Adequate knowledge and positive attitude of the medical and dental students towards the stem cells and their utilization in medical science is extremely important keeping in view the ever-increasing potential of stem cells in the medical field. The present study was planned to assess the knowledge and attitude of the medical and dental students towards stem cells and their applications in medical science. Methods This cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The results showed that majority of the respondents were aware of the existence of stem cells which are in agreement with the awareness studies done in Saudi Arabia 9 and Malaysia. 10 The neglect of medical students regarding the importance of their incorporation in the basic medical research creates a gap between the basic medical researchers and the clinicians, such a fact can impede designing translational studies that eventually can shift stem cells to clinical settings.…”
Section: Discussionsupporting
confidence: 87%
“…The results showed that majority of the respondents were aware of the existence of stem cells which are in agreement with the awareness studies done in Saudi Arabia 9 and Malaysia. 10 The neglect of medical students regarding the importance of their incorporation in the basic medical research creates a gap between the basic medical researchers and the clinicians, such a fact can impede designing translational studies that eventually can shift stem cells to clinical settings.…”
Section: Discussionsupporting
confidence: 87%
“…The KAIMRC Umbilical Cord Blood Bank is a non-profit public bank that provides hematological stem cells for patients in need and research purposes (9,10,19). Notably, the National Guard Health Affairs established The Saudi Stem Cell Donor Registry (SSCDR) in 2011, which is the first stem cell donor registry in the Middle East aimed to increase matching rates for patients (10,20,21). However, there is a general lack of knowledge among the Saudi population about the availability of such reliable centers and the services they provide (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a general lack of knowledge among the Saudi population about the availability of such reliable centers and the services they provide ( 9 ). A more recent survey conducted by Almaeen et al in 2021, has also shown that up to two-thirds of participants were unaware of these centers ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…We discovered a strong positive association between knowledge and attitudes in the current study, which is consistent with previous studies published in Saudi Arabia. 25 Although the knowledge level was moderate for most of the questions, the attitude to uplifting the knowledge and enhancing awareness were high. Our findings are in disagreement with a study done earlier 19 on Malaysian nursing students where a poor correlation between knowledge and attitude was noted that they attributed to being influenced by religious and cultural issues.…”
Section: Discussionmentioning
confidence: 96%